Analisis pemberdayaan masyarakat melalui Program Gerakan Desa Ikut Sejahtera (GaDIS) di Kabupaten Pesawaran - Dendy Kaligis; Wirman Syafri; Mansyur Mansyur (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2020)
This research, in general, would like to describe the implementation of community empowerment by the Regional Government of Pesawaran District through a policy that is the Village Prosperity Movement Program, or often known as the GaDIS Program. This program is installed with a big hope and dream to encourage the village's independence in managing its potential, assets and wealth. The GaDIS Program is a financial stimulant assistance program for the Village Government which will be included as a capital investment for Village Owned Enterprises (BUMDes) of 100 million Rupiah starting in 2017. In this study, the design / research method used by the author is a qualitative method. The data used in this study are qualitative data that is primary data and secondary data. Primary data is processed from observations and interviews. Whereas secondary data was obtained from literature review / documents. The results of this study illustrate the implementation of the GaDIS Program which is well-organized, systematic, based on villages that excel and prioritizes business types or potentials that are based on village deliberations. Indirectly has a positive effect by encouraging some improvements as the goal of community empowerment is defined by Mardikanto (2018: 111), namely improving education, improving accessibility, improving actions, improving institutions, improving business, improving income and improving society. This is at least illustrated in the implementation of the GaDIS Program in 3 (three) villages, namely Wates, Mulyosari and Gunung Rejo, Way Ratai Districts.But on the other hand the lack of institutional strengthening and the low human resource capacity of BUMDesa administrators, as well as the low accessibility and actions, also led to low improvements in business, income and community improvement. This was at least experienced by the Caringin Village of Way Ratai District which was found by researchers in the field. Some obstacles faced in the implementation of the GaDIS program are divided into 2 (two) main obstacles, namely: First: Internal barriers consisting of limited human resource capabilities, weak BUMDes institutions, distribution delays, lack of optimal monitoring and evaluation, Second: External barriers consisting of the absence of BUMDes cooperation and partnership networks, the lack of assistance, and the lack of market access. Determinant factors that strengthen the course of the GaDIS Program include BUMDes management commitment, community awareness and cohesiveness in running the GaDIS program.